TREN SAMBARAN PETIR CLOUD TO GROUND KOTA BALIKPAPAN TAHUN 2016-2018 - Agfanny, Ferruzi; Djayus, Djayus; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2020)
Lightning strikes are very dangerous natural events and can cause significant damage such as fires. Apart from causing lightning strikes, damage can also result in death if contact with living things. Because it is very dangerous, it is necessary to have a reference regarding the level of threat of lightning strikes that occur in the study area. The purpose of this research is to determine the level of lightning threat in the city of Balikpapan in the period 2016 to 2018, to determine the trend or trend of lightning strikes each year. The 2016-2018 lightning strike data obtained from the NexStrom software and Lighting Detector 2000 is a type of Cloud to Ground lightning that is struck directly to the ground and is a lightning hazard for life, then this lightning strike data is processed to find the value of the level of lightning strikes. which occurred in the city of Balikpapan in 2016- 2018. The results of this study found that the average threat level of Balikpapan City lightning strikes and the value of the threat of lightning strikes in 2016-2018.